Leader personality and team adaptive performance in virtuality contexts: how extraversion and openness to experience impact virtual teams - König, Moana (2021)
At the latest, since a global pandemic has propelled individuals into home office, team virtuality has become the new normality. This thesis examined the mediating mechanisms team perceived virtuality in the relationship between leader personality and team adaptive performance. The model was tested in a sample of 37 teams (163 individuals) with different degrees of team virtuality. While leader extraversion did not predict higher team proximity, leader openness to experience predicted increased communication effectiveness in teams with a high degree of structural virtuality. Differently as assumed by prior findings, extraversion and openness to experience in leaders did not increase team adaptive performance. The findings suggest that the existing big-five personality framework is not sufficient to explain leadership and team performance in virtual teams. They also offer new insights into the mechanisms of team perceived virtuality.